Rainfastness of Insecticides Used to Control Spotted-Wing Drosophila in Tart Cherry Production - Ignatius P. Andika; Christine Vandervoort; John C. Wise (Insects, 2019)
Tart cherry production is challenged by precipitation events that may reduce crop protection against spotted-wing drosophila (Drosophila suzukii) (SWD). Due to SWD’s devastating impacts on yield, growers are often faced with the option of insecticide reapplication. Semi-field bioassays were used to assess simulated rainfall effects towards adult mortality, immature survival, and residue wash-off from different plant tissues for several compounds. Tart cherry shoots were treated with 0, 12.7 or 25.4 mm of simulated rainfall and infested with SWD for 5 days. Adult mortality was recorded 1, 3, and 5 days after shoots were infested, while immature stage individuals were counted 9 days after the first infestation day. All insecticides demonstrated higher adult mortality and lower immature survival compared with the untreated control at 0 mm of rainfall. Adult mortality and immature survival caused by phosmet, zeta-cypermethrin, and spinetoram were adversely affected by simulated rainfall. In all bioassays, acetamiprid was the least affected by simulated rainfall. Residue analysis demonstrated phosmet and spinetoram residues to be the most sensitive to wash-off. This study demonstrates different rainfall effects on SWD control for several compounds. This information may provide a basis for making an informed decision on whether reapplication is required.